Análise da produção de lodo de esgoto e da capacidade de disposição do aterro sanitário do Aurá na região metropolitana de Belém para os próximos 20 anos - CUNHA, Débora Suely Anjos (Universidade Federal do Pará, 2017)
Belém Metropolitan Region has few and incomplete informations about production and destination of sewage sludge, because just little part of the sludge generated in septic tank and collective Sewage Works is throwed away without control in Aurá Sanitary Landfill. Because of this, is usual to throw the sludge in water bodies and in the ground, worsen the problems of pollution/contamination in the urban areas. Therefore, this work has the objective of analyzing the increase of production of sludge and evaluate the impact in the Aurá Sanitary Landfill. The search was developed in Belém Metropolitan Region, composed by Belém, Ananindeua, Benevides, Marituba and Santa Bárbara do Pará. It was divided in 2 stages. In the first stage it was estimated the production of the sludge (brute and drained) of septic tanks and in the collective Sewage Works during 2009 to 2030, and the second one was the availability of an area to disposal in the Aurá Sanitary Landfill. In the period studied, it was verified that by the way of the increase of the content of sludge drainage doesn’t has too many impact in the content of the residence solid waste, the deficiency of the available areas in the Aurá Sanitary Landfill is a problem that has to be solved as soon as possible, otherwise residence solid waste and sewage sludge produced in Belém Metopolitan Region won’t be well disposal, as a matter of fact that the prevision is the fast implicate of the free content of Aurá Sanitary Landfill.